KRITERIA ASAS PEMISAHAN HORIZONTAL TERHADAP PENGUASAAN TANAH DAN BANGUNAN - Dyah Devina Maya Ganindra; Faizal Kurniawan (Yuridika, 2017)
The law of The National Land embrace the horizontale scheiding. The horizontale scheiding declare that buildings and plants are not part of the land, it results that ownership of land will not automatically include ownership of the buildings and plants above. And it also means that a legal act against a land will not involve a legal act against the buildings and plants. The existence of the horizontale scheiding could be used to deceives any parties. Then the criteria of horizontale scheiding towards land and/or building’s tenure is necessary to be ascertained before giving legal protection to the parties since both of The Law of the National Land and Burgerlijk Wetboek haven’t give a clear explanation about it. Control of land and buildings in the Burgerlijk Wetbook (BW) adheres to the principle of attachment or which is also referred to as the principle of natrekking / accessie principle. In this principle, the buildings and plants that exist on the ground constitute a unity, more details, buildings and plants are part of the land concerned. Land tenure by itself will also include control over existing buildings and plants and legal acts of land by itself will also include existing buildings and plants.